Nitrogen precursor-mediated construction of N-doped hierarchically porous carbon-supported Pd catalysts with controllable morphology and composition. (15th April 2020) - Pu, Chun; Zhang, Jie; Chang, Ganggang; Xiao, Yueyang; Ma, Xiaochen; Wu, Jian; Luo, Tingting; Huang, Kexin; Ke, Shanchao; Li, Jiaxin; Yang, Xiaoyu
Abstract: Nitrogen-doped carbon-supported metal catalysts are of considerable significance in a diverse range of applications. However, the controllable synthesis of morphology and composition of carbon support materials, in turn, the particle size of supported metal nanoparticles (NPs) is still a great challenge. Herein, nitrogen precursors-mediated synthesis of N-doped hierarchically porous carbon (HPC) with controlled morphology and composition by using MOF as sacrificial template has been demonstrated for the first time. By simply varying the category of nitrogen precursors that with different chemical environment, the morphology, nitrogen configurations and hydrophilicity of the resulted HPC can be effectively tuned. Particularly, the delicate honeycomb-like morphology, the largest amount of nitrogen dopants and excellent wettability of HPC-DCD (dicyandiamide) can effectively stabilize, isolate and disperse the Pd NPs to yield highly dispersed Pd NPs. More importantly, the resulted Pd@HPC-DCD showed excellent catalytic activity and stability toward the hydrodeoxygenation of vanillin in aqueous solution with >99% yield, as well as good universality toward a series of unsaturated hydrocarbons catalyzed by using H2 or formic acid as hydrogen source in aqueous reaction. Such excellent catalytic performance of Pd@HPC-DCD in aqueous solution can be attributed to the hierarchical structure, well-dispersed Pd sites, as well as the favorable hydrophilicity. Graphical abstract: Image 1